Finance and Development, March 1978. (Finance and Development; Finance and Development, 1978)
This paper highlights that 1977 was an eventful year for the IMF. Drawing on the IMF's resources during 1977 totaled more than SDR 3.4 billion. These were accompanied by a record volume of repurchases, which reduced the total net drawings for the year to SDR 427 million. At the end of 1977, total net drawings on the IMF since its inception were equivalent to about SDR 15.5 billion. In 1977, the IMF also carried out its gold sales to members at SDR 35 per ounce under the IMF's 'restitution' program.